Baseline Neurotracker performance does not correlate to overall season sport performance in university varsity athletes - Acquin, Jean-Michel; Giguère-Lemieux, Elizabeth; Deschamps, Alexandre; Glaude-Roy, Julien; Brunelle, Jean-François; Fait, Philippe; Corbin-Berrigan, Laurie-Ann (Frontiers in Sports and Active Living, 2025)
IntroductionThis study examined the relationship between preseason Neurotracker performance and sports performance in university varsity male ice hockey and female volleyball athletes.MethodsNeurotracker, a 3D multiple object tracking task, was used to assess perceptual-cognitive abilities. The association between these abilities and sport statistics was assessed through correlations.Results48 university varsity athletes completed a Neurotracker baseline assessment every preseason between 2019 and 2022, and competed in male ice hockey or female volleyball regular seasons. No significant correlations were found for all sports statistics in female volleyball athletes and male ice hockey except for total penalty minutes (r =  -,40, p < 0,05) and penalty minutes per game (r =  -,39, < 0,05) in male ice hockey.DiscussionThe findings indicate that Neurotracker performance is not associated with sports performance. Further research would be interesting to explore more specific to perceptual-cognitive skills sports statistics in this context.